2007
DOI: 10.1002/ijc.23125
|View full text |Cite
|
Sign up to set email alerts
|

Beyond foreign‐body‐induced carcinogenesis: Impact of reactive oxygen species derived from inflammatory cells in tumorigenic conversion and tumor progression

Abstract: Foreign-body-induced carcinogenesis is a traditional, maybe old, way of understanding cancer development. A number of novel approaches are available today to elucidate cancer development. However, there are things we learn from the old, and thus I bring out some examples of various clinical cases and experimental models of foreign-body-induced tumorigenesis. What is notable is that the foreign bodies themselves are unrelated to each other, whereas commonly underlying in them is to induce inflammatory reaction,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
70
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 92 publications
2
70
0
Order By: Relevance
“…Although fiber dimensions, biopersistence, oxidative stress and inflammation have all been implicated, (7)(8)(9)(10)(11)(12) the exact mechanisms of pleural pathogenesis are unclear. According to a pathogenesis paradigm suggested by Donaldson et al,…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although fiber dimensions, biopersistence, oxidative stress and inflammation have all been implicated, (7)(8)(9)(10)(11)(12) the exact mechanisms of pleural pathogenesis are unclear. According to a pathogenesis paradigm suggested by Donaldson et al,…”
mentioning
confidence: 99%
“…(1)(2)(3)(4)(5)(6) Pleural plaque and malignant mesothelioma are characteristic lesions in asbestos-exposed humans. Although fiber dimensions, biopersistence, oxidative stress and inflammation have all been implicated, (7)(8)(9)(10)(11)(12) the exact mechanisms of pleural pathogenesis are unclear. According to a pathogenesis paradigm suggested by Donaldson et al, (2) asbestos fibers penetrate into the pleural cavity from the alveoli and deposit in the pleural tissue.…”
mentioning
confidence: 99%
“…Rajkovi, et al described a case of gossypiboma discovered 40 years after index surgery as the cause for chronic lumbar back pain [6]. As a consequence of the inflammatory process introduced by retained surgical bodies, sarcomas developing from chronic inflammatory tissue have been reported throughout the literature [10][11][12]. In the presented case, the exudative process led to migration of surgical gauze to the distal medial thigh over a period of 15 years.…”
Section: Discussionmentioning
confidence: 74%
“…36 Tumor development is said to depend on the host's immunological reaction and its derived intermediate reactive substances to the foreign bodies. 35 We have revealed that ROS are commonly formed in QR-32 cells after co-culture with either hydrophilic or hydrophobic nano-TiO 2 . ROS generation by TiO 2 is a well-known phenomenon 37 and the feature has been used for antibacterial activity against both Gram-negative and -positive bacteria.…”
Section: Discussionmentioning
confidence: 92%
“…The influence of material's hydropathy has been pointed out in foreign-body-induced carcinogenesis, which may be fundamentally same in fine particle-related carcinogenesis. 35 In experimental foreign body-induced carcinogenesis, subcutaneous implantation of hydrophobic membranes in mice develops more autologous tumors than those obtained with hydrophilic ones. 36 Tumor development is said to depend on the host's immunological reaction and its derived intermediate reactive substances to the foreign bodies.…”
Section: Discussionmentioning
confidence: 99%